Telework: Solution or obstacle? Perceptions of Art Faculty teachers - Chavez-Somoza, Alicia Roxana (2024)
Objective. To identify the contribution of telework to the professional field of graduates from artistic and creative careers. Methods. A non-experimental design was applied. The research was basic and descriptive in nature. The population consisted of faculty members from two national universities and two higher education schools in Lima, Peru, while the sample included 80 faculty members teaching artistic careers. Data collection was conducted using two questionnaires, each containing 20 questions, from which a descriptive analysis was performed. Results. There is a positive contribution of telework, as most respondents stated that remote work enables professionals in artistic careers to develop in different areas, with better professional and salary recognition. Conclusion. Telework positively contributes to the labor field of artistic careers, overcoming initial challenges following the COVID-19 pandemic, supported by innovation and technology